Of a vigorous and manly race some notes on Ilocano vernacular literature - Foronda, Jr., Marcelino A. (1976)
Ilokano literature is one of the most developed literatures in the Philippines. It is also the only Philippine vernacular writing which is being developed by an active group outside of the country. This paper is about how Ilokano literature developed from before the Spanish colonial period up to the present. It notes the different Ilokano literatures, their works and the different challenges they faced in their efforts to produce literary works in their vernacular.
Includes bibliographical references.